KOMBINASI KAPASITAS KEBIJAKAN DAN MODAL SOSIAL DALAM REVITALISASI SUNGAI MELALUI PROGRAM SIDORESIK - Muhammad Affandi Trihusada (Journal Publicuho, 2025)
Sidoarjo, as a city located in the delta area of two major rivers, faces flooding challenges every year. River revitalisation was carried out by the Sidoarjo local government as an effort to overcome flooding problems in the region. To maintain the function of the revitalised river, the Sidoarjo Revitalisation of River Function (Sidoresik) program was presented by involving community participation to maintain river cleanliness and ecological functions.  This study aims to analyse policy capacity and community participation in supporting the success of the Sidoresik program. The research was conducted using a descriptive qualitative approach. The data collection technique used the literature study method. The results show that the river revitalisation program through Sidoresik is not only beneficial in maintaining river cleanliness and overcoming floods, but also in creating new public spaces that can be used for tourism, sports, environmental education, MSME development, and opening new economic opportunities for residents. The research also confirms the role of policy capacity and community participation in the Sidoresik program in presenting policies that can provide benefits to the community.